Identifying Children at Risk of Malignant Bordetella pertussis Infection. Issue 1 (January 2017) - Ganeshalingham, Anusha; McSharry, Brent; Anderson, Brian; Grant, Cameron; Beca, John
Abstract : Objective: To identify factors associated with malignant pertussis. Design: A retrospective case notes review from January 2003 to August 2013. Area under the receiver-operator characteristic curve was used to determine how well vital sign and white cell characteristics within 48 hours of hospital presentation identified children with malignant pertussis. Setting: The national children's hospital in Auckland, New Zealand. Patients: One hundred fifty-two children with pertussis. Measurements and Main Results: There were 152 children with confirmed pertussis identified, including 11 children with malignant pertussis. The area under the receiver-operator characteristic curve was 0.88 (95% CI, 0.78–0.97) for maximum heart rate. The optimal cut-point was 180 beats/min, which predicted malignant pertussis with a sensitivity of 73% and a specificity of 91%. The area under the receiver-operator characteristic curve was 0.92 (95% CI, 0.81–1.0) for absolute neutrophil count, 0.85 (95% CI, 0.71–0.99) for total WBC count, 0.80 (95% CI, 0.63–0.96) for neutrophil-to-lymphocyte ratio, and 0.77 (95% CI, 0.58–0.92) for absolute lymphocyte count. All children with malignant pertussis had one or more of heart rate greater than 180 beats/min, total WBC count greater than 25 × 10 9 /L, and neutrophil-to-lymphocyte ratio greater than 1.0 with an area under the receiver-operator characteristic curve of 0.96 (95% CI, 0.91–1.0) for a multivariate model that included these three variables. Conclusions: Clinical predictors of malignant pertussis are identifiable within 48 hours of hospital presentation. Early recognition of children at risk of malignant pertussis may facilitate early referral to a PICU for advanced life support and selection for trials of investigational therapies.